Rapid Genetic Screening for Hemochromatosis Using Automated SSCP-Based Capillary Electrophoresis (SSCP-CE). (June 1999) - Bosserhoff, A.-K.; Seegers, S.; Hellerbrand, C.; Schölmerich, J.; Büttner, R.
Hereditary hemochromatosis (HHC) represents an autosomal recessive disease in which increased iron absorption causes iron overload and irreversible tissue damage. The recently detected association between two point mutations in the HFE gene on chromosome 6p and HHC has made it possible to screen for the disease before the onset of irreversible tissue damage. Conventional genetic testing is based on restriction fragment-length polymorphisms (RFLP) using two endonuclease recognition sites in codon 63 or 282, respectively. In this study, we have adapted single-strand conformation polymorphism analysis for capillary electrophoresis (SSCP-CE) to detect homozygote or heterozygote point mutations. Two HFE gene fragments spanning codons 63 and 282 were amplified by a duplex PCR using genomic DNA from peripheral blood or from tissue sections of paraffin-embedded liver biopsies as template. Thereby, rapid genotyping of both HFE mutations was achieved with a single PCR, omitting the need of further analysis by restriction digest. Eighty-five patients with liver disease and/or suspected iron overload were genotyped using SSCP-CE, and all results were verified by conventional RFLP analysis. In summary, SSCP-CE proved to be a reliable, cost-effective, sensitive and rapid method for genotyping HFE mutations. This method will further facilitate high-throughput genetic screening using capillary array electrophoretic devices.